NETFLIX: A STUDY OF COMPETITIVE MARKETING STRATEGIES TO BOOST THE CUSTOMER BASE (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
This case study investigates Netflix's competitive marketing strategies and their effectiveness in expanding and retaining customer base in the increasingly crowded streaming entertainment market. The study analyzes Netflix's evolution from a DVD rental service to a global streaming giant, examining key marketing strategies including content localization, original programming investment, data-driven personalization, and competitive pricing models. The research evaluates how Netflix has successfully competed against traditional media companies and emerging streaming platforms through innovative marketing approaches, strategic partnerships, and technology-driven customer engagement. Through detailed analysis of customer acquisition costs, retention rates, and market share data, the study assesses the return on investment of various marketing initiatives. The case explores Netflix's global expansion strategies, examining how the company adapts its marketing mix for different geographical markets while maintaining brand consistency. The findings provide insights into how digital platforms can leverage technology, content strategy, and customer analytics to build sustainable competitive advantages in highly contested markets.
Keywords: streaming services; competitive strategy; customer acquisition; digital marketing; content marketing